Role of Toxic Elements in Chronic Kidney Disease - Fevrier-Paul, Adwalia (J Health Pollut, 2018)
BACKGROUND. The kidney is central to many complex pathways in the body and kidney injury can precipitate multiple negative clinical outcomes. The resultant effect on nutrition and elemental body burden is bi-directional, confounding the very complex pathways that maintain homeostasis. These elemental changes themselves increase the risk of nutritional and biochemical disturbances. OBJECTIVES. The aim of the present study was to describe how toxic elements interface with complications of chronic kidney disease (CKD). METHODS. The present review included studies focusing on the molecular mechanisms induced by exposure to elements with known nephrotoxic effects and associated health complications in CKD patients. DISCUSSION. Many non-essential elements have nephrotoxic activity. Chronic injury can involve direct tubular damage, activation of mediators of oxidative stress, genetic modifications that predispose poor cardiovascular outcomes, as well as competitive uptake and element mobilization with essential elements, found to be deficient in CKD. Cardiovascular disease is the most common cause of mortality among CKD patients. Oxidative stress, a common denominator of both deficient and excess element body constitution, underlies many pathological derivatives of chronic kidney disease. Bone disorders, hematological dysfunction and dysregulation of acid-base balance are also prevalent in kidney patients. The largest contribution of toxic element body burden results from environmental exposure and lifestyle practices. However, standard medical therapies may also potentiate toxic element accumulation and re-injury of vulnerable tissue. CONCLUSIONS. For CKD patients, the cumulative effect of toxic elements persists throughout the disease and potentiates complications of CKD. Medical management should be coordinated between a medical team, dietitians and clinical researchers to mitigate those harmful effects. COMPETING INTERESTS. The authors declare no competing financial interests